Pemberdayaan UMKM Melalui Webinar Strategi Promosi Online Berbasis Konten TikTok: Studi Kasus Webinar GASPOL - Siti Nurchaliza Panai; Fitria Azizah Potabuga; Siti Mayasari Pakaya; Muhammad Akram Mursalim; Arif Ridha (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
The digital transformation has created both challenges and opportunities for Micro, Small, and Medium Enterprises (MSMEs), particularly in the context of marketing and promotion. This article examines the implementation of a webinar entitled “GASPOL: Exploring Online Promotion Strategies through TikTok Content” as a model of MSME empowerment based on digital education. The activity was organized by the Regional Small Medium Enterprise Service (RSMES) unit of Telkom Regional V involved the direct participation of 150 participants from MSME actors and 31 members of the public with an interest in contemporary marketing strategies. The approach utilized systematic planning, the selection of competent speakers, the preparation of needs-based instructional materials, and both qualitative and quantitative evaluations of participant satisfaction. The webinar was conducted online and presented content on digital branding, storytelling techniques, and the strategic use of TikTok as a promotional tool. The results demonstrated high participant engagement, optimal achievement of key performance indicators (KPIs), and strong participant satisfaction with the relevance and applicability of the material. These findings affirm that digital education interventions using a humanistic approach can effectively strengthen the adaptive capacity of MSMEs in a dynamic digital business landscape. This article offers both conceptual insights and practical contributions for the development of technology-based community learning models within the MSME ecosystem.